1986
DOI: 10.1136/hrt.55.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dissection during pregnancy.

Abstract: SUMMARY Aortic dissection occurred in a nineteen year old woman during the thirty seventh week of pregnancy. Immediate elective delivery of a normal baby by caesarean section was followed by aortic root replacement 48 hours later. It was decided not to proceed immediately to operation on the aortic root because it was believed that the anticoagulation necessary for cardiopulmonary bypass might provoke dangerous haemorrhage from the raw placental site. Case reportA nineteen year old woma-n booked in for her fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The literature retrieval yielded 96 reports, comprising 85 case reports and 11 case series or original articles, with 122 patients . Mean patient age (n = 120) was 31.6 ± 4.7 years (range, 19–43 years; median, 31.5 years) on admission.…”
Section: Resultsmentioning
confidence: 99%
“…The literature retrieval yielded 96 reports, comprising 85 case reports and 11 case series or original articles, with 122 patients . Mean patient age (n = 120) was 31.6 ± 4.7 years (range, 19–43 years; median, 31.5 years) on admission.…”
Section: Resultsmentioning
confidence: 99%
“…[3] Chronic systemic hypertension is the most common risk factor, followed by connective tissue diseases such as Marfans syndrome and Ehlers Danlos syndrome. [4] Our patient had no clinical signs of connective tissue disease. One unique finding in this patient was the presence of normal peripheral pulses.…”
mentioning
confidence: 63%
“…This is because the use of anticoagulant is equired for the surgery; and if anticoagulant is used right after the delivery, uterine hemorrhage should be considered. Pumphyrey performed a surgery for the aortic dissection 48 hours after a cesarean section on the patient of 37 weeks gestation with DeBakey type II [ 12 ]. However, Snir et al [ 13 ] reported that surgery for aortic dissection was performed immediately after the cesarean section.…”
Section: Discussionmentioning
confidence: 99%